2003
DOI: 10.1021/jp034411o
|View full text |Cite
|
Sign up to set email alerts
|

ArF Laser-Induced Chemical Vapor Deposition of Polythiene Films from Carbon Disulfide

Abstract: Laser photolysis at 193 nm of gaseous carbon disulfide into CS and S in the absence and excess of N 2 is controlled by two-photon-induced depletion of CS 2 and affords chemical vapor deposition of (CS) n polymer and S n . The proposed polymerization mechanism of CS is explained by an intermediacy of C 2 S 2 species. The (CS) n polymer contains S-centered radicals that are stable in air and withstand heating in a H 2 atmosphere. Its structure is contributed by >CdS, >CdC<, S 2 CdCS 2, , -C-(CdS)sS-, -Ss(CdS)sS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 67 publications
1
24
0
Order By: Relevance
“…We have previously shown that laser-induced codecomposition of metal and chalcogene progenitors, leading to gas-phase formation of metal and chalcogene clusters, is suitable for chemical vapor deposition of nanosized metal chalcogenides. [10,[18][19][20] Continuing our studies on laserinduced chemical vapor deposition of polythiene [6] and CS 2 /C 2 H 4 co-polymer, [8,9] we now report on ArF laser irradiation of gaseous carbon disulfide-silane mixtures and show that this process affords chemical vapor deposition of SiS-containing poly(thiacarbosilane)s. These materials are the first example of SiS/polymer composites.…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…We have previously shown that laser-induced codecomposition of metal and chalcogene progenitors, leading to gas-phase formation of metal and chalcogene clusters, is suitable for chemical vapor deposition of nanosized metal chalcogenides. [10,[18][19][20] Continuing our studies on laserinduced chemical vapor deposition of polythiene [6] and CS 2 /C 2 H 4 co-polymer, [8,9] we now report on ArF laser irradiation of gaseous carbon disulfide-silane mixtures and show that this process affords chemical vapor deposition of SiS-containing poly(thiacarbosilane)s. These materials are the first example of SiS/polymer composites.…”
Section: Introductionmentioning
confidence: 78%
“…CS þ S, [1][2][3][4][5] ), or be collisionally de-excited by SiH 4 (and N 2 ) molecules. The former route implies formation of elemental sulfur and polythiene [6] and the latter is in line with the formation of a (CS 2 ) n polymer (e.g. [8,9,23,24] [25,26] ) and decomposition of silylene (producing H 2 and H/Si agglomerates) together with reaction of silylene with CS 2 [27] and transient formation of silanethione [28] are other plausible reactions.…”
Section: Gas-phase Photolysis and Volatile Productsmentioning
confidence: 84%
See 3 more Smart Citations